2006
DOI: 10.1182/blood-2006-05-024414
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index does not influence pharmacokinetics or outcome of treatment in children with acute lymphoblastic leukemia

Abstract: There is conflicting information about the influence of body mass index (BMI) on the pharmacokinetics, toxicity, and outcome of chemotherapy. We compared pharmacokinetics, outcome, and toxicity data across 4 BMI groups (underweight, BMI < 10th percentile; normal; at risk of overweight, BMI > 85th and < 95th percentile; overweight, BMI > 95th percentile) in 621 children with acute lymphoblastic leukemia (ALL) treated on 4 consecutive St Jude Total Therapy studies. Chemotherapy doses were not adjusted to ideal B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 38 publications
1
98
1
4
Order By: Relevance
“…38 In our study, overweight children received chemotherapy doses based on actual weight (and not "ideal weight"), which could lead to increased toxicity. This speculation is in part contrasted by Hijiya et al 39 who have shown that in pediatric ALL, there is no statistical difference in pharmacokinetics of cytarabine between normal and overweight patients. Previous studies have found increased TRM in overweight 12 and obese 13 patients with AML resulting in poorer outcome for this group; in this cohort, however, none of 9 TRM cases in children over one year of age were overweight.…”
Section: A B C Dcontrasting
confidence: 51%
“…38 In our study, overweight children received chemotherapy doses based on actual weight (and not "ideal weight"), which could lead to increased toxicity. This speculation is in part contrasted by Hijiya et al 39 who have shown that in pediatric ALL, there is no statistical difference in pharmacokinetics of cytarabine between normal and overweight patients. Previous studies have found increased TRM in overweight 12 and obese 13 patients with AML resulting in poorer outcome for this group; in this cohort, however, none of 9 TRM cases in children over one year of age were overweight.…”
Section: A B C Dcontrasting
confidence: 51%
“…All these factors might produce variations in drug pharmacokinetics; 34 however, the impact of weight status on pharmacokinetics and pharmacodynamics remains under debate in pediatric oncology as there are conflicting reports. 5,36 In the current study underweight patients had a higher incidence of relapse, but interestingly, did not experience many (toxic) events as the event-free survival was similar for both BMI groups (underweight or not underweight). Our Weight influences outcome in pediatric ALL haematologica | 2015; 100 (1) 67 hypothesis is that the observed lack of serious toxicity in combination with the higher incidence of relapse in underweight patients may be related to minor delays and mild dosage deviations of treatment which were based on doctors' choice.…”
Section: Discussionmentioning
confidence: 80%
“…Studies that showed that baseline BMI was not associated with outcome included small numbers of patients in BMI subgroups, or only analyzed the influence of being overweight on survival. [5][6][7][8]13 Studies that reported baseline undernourishment as a determinant of impaired survival were mostly conducted in developing countries or had small numbers in the BMI subgroups. [9][10][11] In those series, patients were, in addition to their disease status and treatment, also coping with additional risk factors for poor outcome such as malnutrition and poor socioeconomic risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Furthermore, although Butturini et al 5 described an association between obesity at diagnosis and survival in children treated for ALL on Children's Oncology Group (COG) protocols, reports from other consortia have not supported this observation. 9,11 Patients underweight at diagnosis in developing countries have been found to have inferior outcomes, 12,13 but this too has not been replicated in studies of patients treated in developed countries. 5,9,11 Therefore, it remains controversial whether a relationship between weight and EFS exists and, if so, whether it applies only to those who are obese or to those who are underweight as well.…”
Section: Introductionmentioning
confidence: 71%